County‐level cumulative environmental quality associated with cancer incidence. Issue 15 (8th May 2017) - Jagai, Jyotsna S.; Messer, Lynne C.; Rappazzo, Kristen M.; Gray, Christine L.; Grabich, Shannon C.; Lobdell, Danelle T.
Abstract : BACKGROUND: Individual environmental exposures are associated with cancer development; however, environmental exposures occur simultaneously. The Environmental Quality Index (EQI) is a county‐level measure of cumulative environmental exposures that occur in 5 domains. METHODS: The EQI was linked to county‐level annual age‐adjusted cancer incidence rates from the Surveillance, Epidemiology, and End Results (SEER) Program state cancer profiles. All‐site cancer and the top 3 site‐specific cancers for male and female subjects were considered. Incident rate differences (IRDs; annual rate difference per 100, 000 persons) and 95% confidence intervals (CIs) were estimated using fixed‐slope, random intercept multilevel linear regression models. Associations were assessed with domain‐specific indices and analyses were stratified by rural/urban status. RESULTS: Comparing the highest quintile/poorest environmental quality with the lowest quintile/best environmental quality for overall EQI, all‐site county‐level cancer incidence rate was positively associated with poor environmental quality overall (IRD, 38.55; 95% CI, 29.57‐47.53) and for male (IRD, 32.60; 95% CI, 16.28‐48.91) and female (IRD, 30.34; 95% CI, 20.47‐40.21) subjects, indicating a potential increase in cancer incidence with decreasing environmental quality. Rural/urban stratified models demonstrated positive associations comparing the highest with the lowest quintiles for all strata, except the thinly populated/rural stratum and in the metropolitan/urbanized stratum. Prostate and breast cancer demonstrated the strongest positive associations with poor environmental quality. CONCLUSION: We observed strong positive associations between the EQI and all‐site cancer incidence rates, and associations differed by rural/urban status and environmental domain. Research focusing on single environmental exposures in cancer development may not address the broader environmental context in which cancers develop, and future research should address cumulative environmental exposures. Cancer 2017;123:2901–8. © 2017 American Cancer Society . Abstract : County‐level cumulative environmental exposures are positively associated with all‐site cancer incidence rates, indicating a potential increase in cancer incidence with decreasing environmental quality. Research focusing on single environmental exposures in cancer development may not address the broader environmental context in which cancers develop. See also pages 2796‐7.